Geração adaptativa de malhas de superfícies paramétricas em paralelo com controle de curvatura - Sombra, Tiago Guimarães (2016)
This work describes a technique for generating parametric surfaces meshes using parallel computing, with distributed memory processors. The input for the algorithm is a set of parametric patches that model the surface of a given object. A structure for spatial partitioning is proposed to decompose the domain in as many subdomains as processes in the parallel system. Each subdomain consists of a set of patches and the division of its load is guided following an estimate. This decomposition attempts to balance the amount of work in all the subdomains. The amount of work, known as load, of any mesh generator is usually given as a function of its output size, i.e., the size of the generated mesh. Therefore, a technique to estimate the size of this mesh, the total load of the domain, is needed beforehand. This work makes use of an analytical average curvature calculated for each patch, which in turn is input data to estimate this load and the decomposition is made from this analytical mean curvature. Once the domain is decomposed, each process generates the mesh on that subdomain or set of patches by a quad tree technique for inner regions, advancing front technique for border regions and is finally applied an improvement to mesh generated. This technique presented good speed-up results, keeping the quality of the mesh comparable to the quality of the serially generated mesh.